1985
DOI: 10.1017/s0022149x00025852
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of some newer broad spectrum anthelmintics against third-stage larvae of Ancylostoma caninum in the mouse

Abstract: The efficacy of eight anthelmintics against Ancylostoma caninum larvae in the skeletal muscles of mice was evaluated. Levamisole (5 × 40 mg kg), thiabendazole (5 × 400mg kg), oxfendazole (5 × 100mg kg), albendazole (5× 1OOmg kg), flubendazole (5 × 200 mg kg), benacil (5 × 200 mg kg) and phenacizole (5 × 200mg kg) showed marked larvicidal activity (98 to 99%). Sch 18099 did not show larvicidal activity even at 5×400 mg kg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Albendazole, flubendazole, benacil, phenacizole, oxfendazole and thiabendazole were found to be effective drugs. We have also shown that these drugs are effective against larvae migrated in the muscles of mice as well (BHOPALE & BHATNAGAR, 1985).…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…Albendazole, flubendazole, benacil, phenacizole, oxfendazole and thiabendazole were found to be effective drugs. We have also shown that these drugs are effective against larvae migrated in the muscles of mice as well (BHOPALE & BHATNAGAR, 1985).…”
Section: Resultsmentioning
confidence: 78%
“…Oxfendazole at the dose level of 5x400 mg/kg showed 88-33% reduction of larvae as compared to untreated control. This drug has also been proved to be effective against larvae of Ancylostoma caninum (BHOPALE & BHATNAGAR, 1985) in mice, larvae of Toxocara canis in brain and muscles of mice (NICHOLAS & STEWART, 1979). Oxfendazole also showed good efficacy in experimental trichinosis of mice (BOLAS FERNANDEZ, 1979;SPALDONOVA & CORBA, 1980).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Albendazole, at the dosage of 500 mg/kg, showed marked larvicidal activity (98-99%) against third stage larvae of Ancylostoma caninum in skeletal muscles of mice (8).…”
Section: Discussionmentioning
confidence: 99%
“…5 Primary Cutaneous Lymphoblastic Lymphoma of Non-B, Non-T Phenotype To the Editor.\p=m-\Lymphoblastic lymphoma (LBL) is a tumor of lymphoid precursors with a lymphomatous presentation. Furthermore, itraconazole seems to be well tolerated with minimal side effects and with much lower toxic effects than ketoconazole.…”
mentioning
confidence: 99%